Composite current collector, secondary battery, and electric device

By setting pores in the metal layer and controlling the porosity and yield strength, the problem of insufficient magnification performance and stability in the composite fluid is solved, and the performance improvement of the secondary battery is achieved.

CN119230837AActive Publication Date: 2024-12-31CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310792261.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

The existing secondary batteries using composite fluid collectors have shortcomings in terms of rate performance and long-term stability, especially the problem of poor rate performance and poor stability of the battery cell.

Method used

By setting pores with a certain pore diameter in the metal layer, the porosity of the metal layer is controlled to be in the range of 3% to 20%, and the yield strength of the composite fluid is controlled to be between 120MPa and 180MPa, so as to increase the two Rate performance and stability of secondary batteries.

Benefits of technology

This method effectively reduces the brittleness of the metal layer, improves the ductility of the composite fluid collection, avoids cracks in the metal layer during processing and battery circulation, and significantly improves the rate performance and long-term stability of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230837A_ABST
    Figure CN119230837A_ABST
Patent Text Reader

Abstract

The invention provides a composite current collector, a secondary battery and an electric device. The composite current collector comprises an organic layer and a metal layer arranged on at least one surface of the organic layer, pores are formed in the metal layer, the pore diameter of at least part of the pores is 10nm-200nm, and the porosity of the metal layer is 3%-20%; the composite current collector satisfies the following relational expression: 0.5 * sigma1 * T < existence > / (T < existence > + T < gold >) < = sigmas < = 0.8 * sigma1 * T < existence > / (T < existence > + T < gold >); wherein sigma 1 is the breaking strength of the organic layer, and the unit is MPa; t is the thickness of the organic layer, and the unit is [mu] m; t gold is the total thickness of the metal layer, and the unit is [mu] m; sigma s is the yield strength of the composite current collector, and the unit is MPa. The composite current collector can improve the rate capability and the stability of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite current collector, a secondary battery and an electrical device. Background Art

[0002] In recent years, as the application scope of secondary batteries becomes wider and wider, secondary batteries are widely used in energy storage power supply systems such as hydropower, thermal power, wind power and solar power stations, as well as in many fields such as electric tools, electric bicycles, electric motorcycles and electric vehicles.

[0003] As secondary batteries have made great progress, higher requirements have been placed on their performance. Secondary batteries using composite current collectors have great advantages in safety, energy density and cost. However, secondary batteries using composite current collectors currently also have problems such as poor rate performance and poor stability of the battery cells.

[0004] Therefore, seeking for secondary batteries with better rate performance and stability using composite current collectors is one of the key areas of focus for those skilled in the art. Summary of the invention

[0005] The present application is made in view of the above-mentioned problems, and one of its purposes is to provide a composite current collector that can improve the rate performance and stability of a secondary battery.

[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a composite current collector, comprising an organic layer and a metal layer disposed on at least one surface of the organic layer;

[0007] The metal layer has pores, at least some of the pores have a pore size of 10 nm to 200 nm, and the porosity of the metal layer is 3% to 20%;

[0008] The composite current collector satisfies the following relationship:

[0009] 0.5*σ1*T 有 / (T 有 +T 金 )≤σ s ≤0.8*σ1*T 有 / (T 有 +T 金 );

[0010] Wherein, σ1 is the fracture strength of the organic layer, in MPa; T 有 is the thickness of the organic layer, in μm; T 金 is the total thickness of the metal layer, in μm; σ s is the yield strength of the composite current collector, in MPa.

[0011] The present application forms a composite current collector from a metal layer and an organic layer, and sets pores with a certain pore size in the metal layer, controls the porosity of the metal layer within a certain range, and controls the yield strength of the composite current collector within a certain range, so that the metal layer of the composite current collector is not prone to cracks during processing and subsequent battery cycles, and the current collector is not prone to breakage, thereby improving the rate performance and stability of the secondary battery.

[0012] In any embodiment, the metal element in the metal layer includes one or more of copper, aluminum, nickel, titanium, platinum, iron, cobalt, chromium, tungsten, molybdenum, magnesium, lead, indium and tin.

[0013] In any embodiment, the metal layer is a metal aluminum layer, and the composite current collector satisfies the following relationship:

[0014]

[0015] Wherein, ρ1 is the average density of the composite current collector, in g / cm 3 ; ρ2 is the density of the organic layer, in g / cm 3 This is more conducive to improving the DC resistance DCR and rate performance of the secondary battery and improving the long-term stability of the secondary battery.

[0016] In any embodiment, the yield strength of the composite current collector is 120 MPa to 180 MPa. In this way, the current collector will not have large cracks, and will not be deformed due to excessive cold pressing extension caused by too low yield strength.

[0017] In any embodiment, the resistivity of the composite current collector is ≤3.5*10 -8 In this way, a thinner metal layer can be used to achieve the same conductive effect, which can improve the energy density and safety of the battery cell.

[0018] In any embodiment, the size of the primary single crystal particles of the metal layer is 35nm to 80nm, the size of the secondary particles in the metal layer is 90nm to 300nm, and the particle size of the secondary particles is greater than the sum of the particle sizes of all the primary single crystal particles constituting the secondary particles. In this way, the crystallinity and connectivity of the metal layer of the current collector can be ensured, the resistance of the battery cell can be reduced, and the micro gaps in the secondary particles can also act as stress release points.

[0019] In any embodiment, the surface roughness of the composite current collector is ≥ 0.2 μm. In this way, the contact between the composite current collector and the active material can be better, the DC resistance DCR of the battery cell can be reduced, and the rate performance of the battery can be further improved.

[0020] In any embodiment, the specific surface area of ​​the composite current collector is ≥ 0.188 m 2 In this way, the contact between the composite current collector and the active material can be better, the DC resistance DCR of the battery cell can be further reduced, and the rate performance of the battery can be further improved.

[0021] In any embodiment, the square resistance growth rate of the composite current collector after 10% stretching and rebounding is ≤5%. In this way, the conductivity of the metal layer can be better guaranteed, and the performance and long-term stability of the battery core can be guaranteed.

[0022] In any embodiment, the square resistance growth rate of the composite current collector after 30% elongation and stretching rebound is ≤10%. In this way, the performance and long-term stability of the battery cell can be further guaranteed.

[0023] In any embodiment, the thickness of a single metal layer is 0.5 μm to 5 μm. In this way, the current collector can have good conductivity and safety issues caused by too thick a metal layer can be avoided.

[0024] In any embodiment, the thickness of a single metal layer is 0.8 μm to 1.5 μm.

[0025] In any embodiment, the single metal layer includes a dense layer and a porous layer, and the pores are located in the porous layer; the dense layer is arranged on the surface of the organic layer, and the porous layer is arranged on the surface of the dense layer away from the organic layer; or the porous layer is arranged on the surface of the organic layer, and the dense layer is arranged on the surface of the porous layer away from the organic layer. In this way, it can further ensure that the battery cell has good interface performance, DC resistance DCR and rate performance; and the dense layer is arranged on the surface of the organic layer, and the porous layer is arranged on the surface of the dense layer away from the organic layer, which can also improve the bonding force between the metal layer and the organic layer, and improve the long-term electrolyte immersion resistance of the composite current collector.

[0026] In any embodiment, the density ρ3 of the dense layer is 2.65 g / cm 3 ≤ρ3≤2.70g / cm 3 The density of the porous layer is ρ4 2.00 g / cm 3 ≤ρ4<2.65g / cm 3 .

[0027] In any embodiment, the thickness of the dense layer is 10% to 50% of the thickness of the corresponding single metal layer; the thickness of the porous layer is 50% to 90% of the thickness of the corresponding single metal layer.

[0028] In any embodiment, the thickness of the dense layer is 100 nm to 500 nm; the thickness of the porous layer is 500 nm to 900 nm.

[0029] In any embodiment, the longitudinal elongation at break and / or the transverse elongation at break of the composite current collector are both ≥ 50%. In this way, the current collector is less likely to break during processing, thereby improving the manufacturing efficiency; and the composite current collector will not break even under large expansion force or large deformation during use in the battery cell.

[0030] In any embodiment, the organic layer includes an organic polymer film, which includes polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene ether, polyphenylene sulfide, polyethylene glycol, polysulfur nitride, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, phenolic resin and one or more of the derivatives, crosslinks and copolymers of the above polymers.

[0031] In any embodiment, the thickness of the organic layer is 1 μm to 20 μm.

[0032] In any embodiment, the thickness of the organic layer is 3 μm to 10 μm.

[0033] The second aspect of the present application provides a secondary battery, comprising the composite current collector of the first aspect of the present application. Thus, the secondary battery has good rate performance and long-term stability.

[0034] A third aspect of the present application provides an electrical device, comprising the secondary battery of the second aspect of the present application.

[0035] The composite current collector of the present application controls the porosity of the metal layer within a certain range and the yield strength of the composite current collector within a certain range by setting pores with a certain pore size in the metal layer; the brittleness of the metal layer in the composite current collector can be reduced, and the composite current collector has moderate ductility, so that the metal layer of the composite current collector is not prone to cracks during processing and subsequent battery cycles, and the current collector is not prone to breakage, which can improve the rate performance and long-term stability of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to better describe and illustrate the embodiments and / or examples of the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments and / or examples currently described, and any of the best modes of these applications currently understood.

[0037] Figure 1 is a schematic structural diagram of a composite current collector according to an embodiment of the present application;

[0038] Figure 2 is a schematic structural diagram of a composite current collector according to another embodiment of the present application;

[0039] Figure 3 is a schematic structural diagram of a composite current collector according to another embodiment of the present application;

[0040] Figure 4 is a longitudinal (MD) tensile curve of a composite current collector according to an embodiment of the present application and a composite current collector with D>2.65;

[0041] Figure 5 is a transverse (TD) tensile curve of a composite current collector according to an embodiment of the present application and a composite current collector with D>2.65;

[0042] Figure 6 This is a photo of the surface cracks on the metal layer of the composite current collector with D>2.65 after 30% longitudinal (MD) stretching;

[0043] Figure 7 This is a photo of the surface cracks on the metal layer of the composite current collector with D>2.65 after 30% transverse (TD) stretching;

[0044] Figure 8 This is a photo of cracks on the surface of the metal layer of the composite current collector according to one embodiment of the present application after being stretched by 30% in the longitudinal direction (MD);

[0045] Fig. 9 This is a photo of cracks on the surface of the metal layer of the composite current collector according to one embodiment of the present application after being stretched in the transverse direction (TD) by 30%;

[0046] Fig.10 is a surface morphology diagram of a pore layer in a composite current collector according to an embodiment of the present application;

[0047] Fig.11 is a surface morphology diagram of a dense layer in a composite current collector according to an embodiment of the present application;

[0048] Fig.12 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0049] Fig.13 yes Fig.12An exploded view of a secondary battery according to an embodiment of the present application is shown;

[0050] Fig.14 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0051] Description of reference numerals:

[0052] 10. Composite current collector; 11. Organic layer; 12. Metal layer; 121. Pores; 122. Dense layer; 123. Porous layer; 5. Secondary battery; 51. Shell; 52. Electrode assembly; 53. Cover plate; 6. Electrical device. DETAILED DESCRIPTION

[0053] Hereinafter, some embodiments of the composite current collector, secondary battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0054] The "range" disclosed in the present application can be defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and any end value can be included or excluded independently, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that the range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are also listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.

[0055] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0056] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0057] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.

[0058] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0059] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "comprise", etc., unless otherwise specified, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. Unless otherwise specified, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A not only includes a1, a2 and a3, but also includes other members". In the present application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0060] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.

[0061] The weight described in this application specification may be μg, mg, g, kg or other weight units known in the chemical industry.

[0062] At present, as secondary batteries have made great progress, higher requirements have been put forward for the performance of secondary batteries. Secondary batteries using composite current collectors have great advantages in safety, energy density and cost. However, secondary batteries using composite current collectors also have problems such as poor rate performance and poor long-term stability of the battery cells. Therefore, seeking a composite current collector that can improve the rate performance and long-term stability of secondary batteries is one of the key areas of focus for those skilled in the art. In this regard, the inventors have discovered a composite current collector that can improve the rate performance and long-term stability of secondary batteries using the composite current collector by setting the structure of the metal layer and the yield strength of the current collector.

[0063] In some of these implementations, see Figure 1 , Figure 2 and Figure 3 In a first aspect of the present application, a composite current collector 10 is provided, comprising an organic layer 11 and a metal layer 12 disposed on at least one surface of the organic layer 11; the metal layer 12 has pores 121, at least part of the pores 121 has a pore size of 10 nm to 200 nm, and the porosity of the metal layer 12 is 3% to 20%; the composite current collector 10 satisfies the following relationship:

[0064] 0.5*σ1*T 有 / (T 有 +T 金 )≤σ s ≤0.8*σ1*T 有 / (T 有 +T 金 );

[0065] Wherein, σ1 is the fracture strength of the organic layer 11, in MPa; T 有 is the thickness of the organic layer 11, in μm; T 金 is the total thickness of the metal layer 12, in μm; σ s is the yield strength of the composite current collector 10, in MPa.

[0066] In the process of cold pressing, roll welding, etc., the metal layer 12 of the traditional composite current collector 10 is prone to cracks, resulting in a decrease in the conductivity of the metal layer 12 of the composite current collector 10, making the direct current resistance (DCR) of the secondary battery larger, affecting the rate performance and long-term stability of the battery; or the ductility of the composite current collector 10 during the cold pressing process is too large, making the pole piece easily deformed and the interface performance degraded, resulting in the DC resistance of the secondary battery gradually increasing during long-term use, and the rate performance and long-term stability are reduced.

[0067] The composite current collector 10 of the present application controls the porosity of the metal layer 12 within a certain range and the yield strength of the composite current collector 10 within a certain range by setting pores 121 with a certain pore size in the metal layer 12; the brittleness of the metal layer 12 in the composite current collector 10 can be reduced, and the ductility of the composite current collector 10 during cold pressing, roll welding, etc. can be moderate. The pores 121 inside the metal layer 12 of the composite current collector 10 can provide stress release points during cold pressing, roll welding, etc., so that the metal layer 12 is not easy to crack; the presence of the pores 121 can reduce the brittleness of the metal layer 12, reduce the elastic modulus, improve the ductility of the metal layer 12, and reduce the yield strength of the composite current collector 10, so that the metal layer 12 can release stress through the pores 121 when subjected to stress (such as stretching and bending) without generating macro cracks; thus, the composite current collector 10 will not generate macro cracks during processing (such as welding, winding) and subsequent battery cycles, ensuring the conductivity of the composite current collector 10, thereby alleviating the increase in DCR during the use of the secondary battery, which is beneficial to improving the rate performance and long-term stability of the secondary battery. The pore size and porosity of the pores 121 in the metal layer 12 are within the above range, which can ensure that the yield strength of the composite current collector 10 is within a suitable range.

[0068] During the stretching process, the final fracture point of the composite current collector 10 is strongly correlated with the fracture strength of the organic layer 11, and the fracture force of the organic layer 11 is basically close to the final fracture force of the composite current collector 10. Therefore, the fracture force and fracture strength of the current collector can be predicted by the fracture force of the organic layer 11, and the fracture strength of the current collector is approximately equal to the fracture strength of the organic layer σ1*T 有 / (T 有 +T 金), the yield strength of the current collector is controlled between the breaking strength*0.5 and the breaking strength*0.8, so that there is still a stretchable distance between the turning point of the tensile curve and the breaking strength of the composite current collector 10 during the stretching process, so that the strength of the current collector slowly rises after the yield strength, making it less likely for the current collector to break, and making the current collector uniformly extended, with a higher elongation at break; and this state of slowly increasing force makes the metal layer bear less force under the same elongation, and the metal layer 12 itself has pores 121 to release stress, so the metal layer 12 is not easy to produce macro cracks, so that the conductivity of the current collector during processing and application in the battery cell is guaranteed. The lower limit of the yield strength of the composite current collector 10 is greater than 0.5 times the breaking strength, so that the yield strength is not too low, and the current collector will not be deformed due to excessive cold pressing extension during the cold pressing process, and the interface performance of the battery cell will decrease, the DCR will increase, and the rate performance will decrease.

[0069] The present application sets pores 121 with a certain aperture in the metal layer 12 of the composite current collector 10, controls the porosity of the metal layer 12 within a certain range, and controls the yield strength of the composite current collector 10 within a certain range; it can reduce the brittleness of the metal layer 12 in the composite current collector 10, so that the composite current collector 10 has moderate ductility, so that the metal layer 12 of the composite current collector 10 is not easy to crack during processing and subsequent battery cycles, and the current collector is not easy to break, which is beneficial to improving the rate performance and long-term stability of the secondary battery. In addition, the ductility of the composite current collector 10 is moderate, and the processing yield of the composite current collector 10 can also be improved, and the broken belt during the processing process can be reduced.

[0070] It should be noted that the pores 121 in the metal layer 12 can be formed by the following method: in the process of depositing the metal layer 12 on the organic layer 11, the single deposition rate is controlled to be greater than 500nm, so that some positions of the metal layer 12 cannot be filled with metal in time during the high-speed production process, thereby retaining certain microscopic pores 121. The existence of these pores 121 will not affect the conductive properties of the current collector, and can provide certain stress release points when the metal layer 12 is subjected to external force, so that the metal layer 12 does not produce macroscopic cracks.

[0071] It can be understood that only some of the pores 121 in the metal layer 12 may have a pore size within the range of 10nm to 200nm, or the pore size of all the pores 121 may be within the range of 10nm to 200nm. When the pore 121 is a spherical pore, the pore size of the pore 121 is the diameter of the spherical pore; when the pore 121 is not a spherical pore, the pore size of the pore 121 is the diameter of a spherical pore with the same volume as the pore 121, that is, the equivalent diameter. The porosity of the metal layer 12 may be, but is not limited to, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%. σ s It can be but not limited to σ1*T 有 / (T 有 +T 金 )’s value.

[0072] In some embodiments, the metal element in the metal layer 12 includes one or more of copper, aluminum, nickel, titanium, platinum, iron, cobalt, chromium, tungsten, molybdenum, magnesium, lead, indium and tin. In other words, the metal layer 12 in the composite current collector 10 can be a metal copper layer, a metal aluminum layer, a metal nickel layer, a metal titanium layer, a metal platinum layer, a metal iron layer, a metal cobalt layer, a metal chromium layer, a metal tungsten layer, a metal molybdenum layer, a metal magnesium layer, a metal lead layer, a metal indium layer and a metal tin layer, or an alloy metal layer formed by two or more of the above metal elements.

[0073] In some embodiments, the metal layer 12 is a metal aluminum layer, and the composite current collector 10 satisfies the following relationship:

[0074] 2.00≤D<2.65;

[0075] Wherein, ρ1 is the average density of the composite current collector 10, in g / cm 3 ; ρ2 is the density of the organic layer 11, in g / cm 3 It can be understood that since the composite current collector 10 is a composite structure of the organic layer 11 and the metal layer 12 , the density at different positions of the composite current collector 10 may be different, and ρ1 represents the average density of the composite current collector 10 as a whole.

[0076] When the metal layer 12 is a metal aluminum layer, the average density ρ1 of the composite current collector 10, the density ρ2 of the organic layer 11, and the total thickness T of the metal layer 12 金 and the thickness T of the organic layer 11 有When the above relationship is satisfied, the density of the metal aluminum layer can be within an appropriate range, the brittleness of the metal layer 12 in the composite current collector 10 can be reduced, and better ductility can be obtained, so that the yield strength of the composite current collector 10 is within an appropriate range, so that the force of the current collector at the beginning of stretching is not too large, and the force of the current collector shows a slow growth trend during the stress process such as stretching; and because the brittleness of the metal layer 12 is reduced, the metal layer 12 is not prone to macro cracks when stretched and extended; with the increase of elongation, the square resistance hardly increases, and the conductivity remains very good; so that the composite current collector 10 can still maintain good conductivity under higher elongation, which can improve the DCR and rate performance of the secondary battery, and improve the long-term stability of the secondary battery.

[0077] When D<2.00, the density of the metal aluminum layer is too poor, there are too many pores 121, or the size of the pores 121 is too large, resulting in the composite current collector 10 having too low elastic modulus and too low yield strength, resulting in excessive cold pressing extension during the cold pressing process, causing the pole piece to easily deform, deteriorating the interface performance of the secondary battery, and thus causing the short-term and long-term performance of the secondary battery to deteriorate.

[0078] When D≥2.65, the density of the metal aluminum layer is too high, the elastic modulus is very high, there is no good stress release point in the metal aluminum layer, and the brittleness of the metal aluminum layer is relatively high, which makes it easy for the metal aluminum layer to crack when subjected to external forces (such as extension, bending, compression, etc.). The conductivity of the metal aluminum layer is weakened and the square resistance is increased, resulting in a decrease in the rate performance and long-term stability of the secondary battery.

[0079] The longitudinal (MD) tensile curve of the composite current collector 10 with D>2.65 and a composite current collector 10 with a value within the range of 2.00≤D<2.65 in the present application is as follows Figure 4 As shown, its transverse (TD) tensile curve is as follows Figure 5 shown.

[0080] Depend on Figure 4 and Figure 5It can be seen that when D<2.00, the brittleness of the metal aluminum layer is too strong, resulting in an excessively high yield strength of the current collector. When stretched, the force reaches a very high value at once, thereby reducing the elongation at break of the current collector and making the metal aluminum layer easily cracked under the action of external force, thereby affecting the conductivity of the composite current collector 10 and the performance of the secondary battery. When D is within the range of 2.00≤D<2.65, the force borne by the current collector during stretching presents a slowly increasing state; the elongation at break of the current collector is significantly improved, and the elongation at break in the MD and TD directions is greater than 40%; and when the current collector is subjected to force, it is not easy to crack, and the conductivity is maintained well, which improves the processing and tolerance window of the current collector, thereby ensuring the conductivity of the current collector during processing and use, and ensuring the performance of the battery cell.

[0081] The surface crack picture of the composite current collector 10 with D>2.65 after 30% longitudinal extension and stretching is shown in the figure. Figure 6 As shown, the surface crack picture of the composite current collector 10 after 30% lateral stretching is as shown in Figure 7 The surface crack picture of the composite current collector 10 with a value of D in the range of 2.00≤D<2.65 after 30% longitudinal stretching is shown in FIG. Figure 8 As shown, the surface crack picture of the composite current collector 10 after 30% lateral stretching is as shown in Fig. 9 shown.

[0082] Depend on Figure 6 and Figure 7 It can be seen that after the composite current collector 10 with D>2.65 was stretched by 30% in the longitudinal direction and 30% in the transverse direction, many cracks appeared on its surface. Figure 8 and Fig. 9 It can be seen that after the composite current collector 10 in the present application is stretched by 30% longitudinally and 30% transversely, there is almost no crack on its surface. The above situation shows that the composite current collector 10 of the present application is not easy to crack when subjected to force, and the conductivity of the composite current collector 10 during processing and use can be guaranteed, and the performance of the battery cell can be guaranteed.

[0083] It is understood that the value of D can be but is not limited to 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, 2.55, and 2.60.

[0084] In some embodiments, the yield strength of the composite current collector 10 is 120MPa to 180MPa. The fracture strength of the organic layer membranes currently used in the composite current collector 10 is generally 200MPa to 300MPa. By controlling the yield strength of the composite current collector 10 within the range of 120MPa to 180MPa, the composite current collector 10 can be suitable for different types of organic layer membranes, so that the composite current collector 10 using different organic layers 11 can produce a higher elongation. By controlling the yield strength of the composite current collector 10 within the above range, the current collector will not produce large cracks, and will not be too cold-pressed and stretched, and the pole piece will not be deformed due to too low a yield strength.

[0085] It can be understood that the yield strength of the composite current collector 10 can be but is not limited to 120 MPa, 125 MPa, 130 MPa, 135 MPa, 140 MPa, 145 MPa, 150 MPa, 155 MPa, 160 MPa, 165 MPa, 170 MPa, 175 MPa, 180 MPa.

[0086] In some embodiments, the resistivity of the composite current collector 10 is ≤3.5*10 -8 The composite current collector 10 has a lower resistivity, which can make the current collector have better conductivity at the same thickness of the metal layer 12. A thinner metal layer 12 can achieve the same conductive effect, which can improve the energy density of the battery cell; and a thinner metal layer 12 also improves the safety of the battery cell.

[0087] In some of the embodiments, the primary single crystal particle size (i.e., grain size) of the metal layer 12 is 35nm to 80nm, the size of the secondary particles in the metal layer 12 is 90nm to 300nm, and the size of the secondary particles is larger than the sum of the sizes of all primary particles constituting the secondary particles; adjacent secondary particles in the metal layer 12 are spaced apart to form pores 121.

[0088] By controlling the primary single crystal particle size of the metal layer 12 of the composite current collector 10 to be between 35nm and 80nm, the crystallinity of the metal layer 12 of the current collector can be ensured; by controlling the size of the secondary particles in the metal layer 12 to be between 90nm and 300nm, the connectivity of the current collector can be ensured. At the same time, the size of the secondary particles is slightly larger than the size of all the primary particles that make up them, indicating that there are certain microgaps between the primary particles in the secondary particles. These microgaps between the primary single crystal particles can play a role similar to that of the pores 121 in the metal layer 12.

[0089] It should be noted that the primary single crystal particle is the XRD diffraction peak, and the size of the primary single crystal particle can be calculated according to the Scherrer formula through the half-peak width, etc.; the size of the secondary particle is tested by surface SEM, and the average value is taken after measuring the sizes of more than 50 secondary particles.

[0090] It can be understood that the primary single crystal particle size of the metal layer 12 in the composite current collector 10 can be but not limited to 35nm, 38nm, 40nm, 42nm, 45nm, 48nm, 50nm, 60nm, 70nm, 75nm, 80nm; the size of the secondary particles in the metal layer 12 can be but not limited to 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm.

[0091] In some embodiments, the surface roughness of the composite current collector 10 is ≥ 0.2 μm. The larger surface roughness of the composite current collector 10 can improve the contact between the composite current collector 10 and the active material, reduce the DC resistance DCR of the battery cell, and further improve the rate performance of the battery.

[0092] In some embodiments, the specific surface area of ​​the composite current collector 10 is ≥ 0.188 m 2 The composite current collector 10 has a large specific surface area, which can also improve the contact between the composite current collector 10 and the active material, further reduce the DC resistance DCR of the battery cell, and further improve the rate performance of the battery.

[0093] In some embodiments, the square resistance growth rate of the composite current collector 10 after 10% elongation and stretching is ≤5%. In this way, the square resistance of the composite current collector 10 after stretching and rebounding is almost non-increasing, further ensuring that the current collector will hardly generate macro cracks during processing, such as cold pressing, thereby ensuring the conductivity of the metal layer 12; and ensuring that the current collector will hardly generate macro cracks during use inside the battery cell, thereby ensuring the performance and long-term stability of the battery cell.

[0094] In some embodiments, the square resistance growth rate of the composite current collector 10 after rebound after 30% elongation is ≤10%. In this way, the square resistance of the composite current collector 10 rebounds almost without growth under greater stretching, ensuring that the current collector will hardly generate macro cracks even under more severe conditions during processing, thereby further ensuring the conductivity of the metal layer 12; and ensuring that almost no macro cracks will be generated during more severe use inside the battery cell (such as high silicon high expansion, high stress, high deformation system), thereby further ensuring the performance and long-term stability of the battery cell.

[0095] In some embodiments, the thickness of the single metal layer 12 is 0.5 μm to 5 μm, and further the thickness of the single metal layer 12 is 0.8 μm to 1.5 μm. In this way, the thickness of the single metal layer 12 is neither too thin nor too thick, which can make the current collector have good conductivity and avoid safety problems caused by too thick metal layer 12. It can be understood that the thickness of the single metal layer 12 can be but is not limited to 0.5μm, 0.8μm, 1.0μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm, 2.0μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3.0μm, 3.2μm, 3.4μm, 3.6μm, 3.8μm, 4.0μm, 4.2μm, 4.4μm, 4.6μm, 4.8μm, 5μm.

[0096] In some embodiments, the composite current collector 10 includes an upper and lower metal layer 12, and the organic layer 11 is located between the upper and lower metal layers 12. It can be understood that in other embodiments, the composite current collector 10 may also have only one metal layer 12, that is, the metal layer 12 is only provided on one side of the organic layer 11.

[0097] In some embodiments, the single metal layer 12 includes a dense layer 122 and a porous layer 123, and the pores 121 are located in the porous layer 123. Figure 2 In some embodiments, the dense layer 122 is disposed on the surface of the organic layer 11, and the porous layer 123 is disposed on the surface of the dense layer 122 facing away from the organic layer 11. Figure 3In other embodiments, the porous layer 123 is disposed on the surface of the organic layer 11, and the dense layer 122 is disposed on the surface of the porous layer 123 away from the organic layer 11. In this way, the metal layer 12 can make the yield strength of the current collector within a suitable range through the mutual matching of the dense layer 122 and the porous layer 123, and the porous layer 123 can ensure that the elongation at break of the current collector is improved and the cold pressing extension is not too large, which can ensure that the metal layer 12 almost does not produce macro cracks when extended, and the conductivity is almost not reduced; it can also ensure that the yield strength is not too low, the cold pressing extension is not too large, and the pole piece does not have too large deformation, and the interface performance, DC resistance DCR and rate performance of the battery cell are guaranteed; in some embodiments, the dense layer 122 is disposed between the organic layer 11 and the porous layer 123, which is also conducive to improving the bonding force between the metal layer 12 and the organic layer 11, and improving the long-term electrolyte immersion resistance of the composite current collector 10. The surface morphology of the porous layer 123 in the composite current collector 10 is shown in FIG. Fig.10 The surface morphology of the dense layer 122 in the composite current collector 10 is shown in FIG. Fig.11 shown.

[0098] The dense layer 122 can be prepared by controlling the single deposition thickness of the metal to be 30 nm to 50 nm and controlling the deposition vacuum to be lower than 1*10 -3 Pa, and control the deposition rate ≤ 10 μm*m / min. The above-mentioned pore layer 123 can be obtained by controlling the single deposition thickness of the metal to be ≥ 500 nm, the deposition rate to be ≥ 5 μm*m / min, and introducing inert gas or nitrogen to make the vacuum degree reach 5*10 -2 Pa is obtained (the flow rate of the inert gas or nitrogen can be 50 mL / min to 100 mL / min).

[0099] In some embodiments, the density ρ3 of the dense layer 122 is 2.65 g / cm 3 ≤ρ3≤2.70g / cm 3 The density ρ4 of the porous layer 123 is 2.00 g / cm 3 ≤ρ4<2.65g / cm 3 It is understood that the density of the dense layer 122 may be, but is not limited to, 2.66 g / cm 3 , 2.67g / cm 3 , 2.68g / cm 3 , 2.69g / cm 3 , 2.70g / cm 3 The density of the porous layer 123 may be, but is not limited to, 2.00 g / cm 3 , 2.05g / cm 3 , 2.10g / cm3 , 2.15g / cm 3 , 2.20g / cm 3 , 2.25g / cm 3 , 2.30g / cm 3 , 2.35g / cm 3 , 2.40g / cm 3 , 2.45g / cm 3 , 2.50g / cm 3 , 2.55g / cm 3 , 2.60g / cm 3 .

[0100] In some embodiments, the thickness of the dense layer 122 is 10% to 50% of the thickness of the corresponding single-layer metal layer 12; the thickness of the pore layer 123 is 50% to 90% of the thickness of the corresponding single-layer metal layer 12. That is, the thickness of the pore layer 123 in the single-layer metal layer 12 is thicker than that of the dense layer 122. In this way, while effectively improving the bonding force between the metal layer 12 and the organic layer 11 and improving the long-term electrolyte immersion resistance of the composite current collector 10, it is more conducive to improving the interface performance, DC resistance DCR and rate performance of the battery cell.

[0101] It can be understood that the thickness of the dense layer 122 can be but not limited to 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50% of the thickness of the corresponding single-layer metal layer 12; the thickness of the porous layer 123 can be but not limited to 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90% of the thickness of the corresponding single-layer metal layer 12.

[0102] In some embodiments, the thickness of the dense layer 122 is 100 nm to 500 nm; the thickness of the porous layer 123 is 500 nm to 900 nm. It can be understood that the thickness of the dense layer 122 can be but not limited to 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, 320nm, 340nm, 360nm, 380nm, 400nm, 420nm, 440nm, 460nm, 480nm, 500nm; the thickness of the porous layer 123 can be but not limited to 500nm, 520nm, 540nm, 560nm, 580nm, 600nm, 620nm, 640nm, 660nm, 680nm, 700nm, 720nm, 740nm, 760nm, 780nm, 800nm, 820nm, 840nm, 860nm, 880nm, 900nm.

[0103] In some embodiments, the longitudinal (MD) elongation at break and the transverse (TD) elongation at break of the composite current collector 10 are both ≥ 40%. In this way, the composite current collector 10 has a large elongation at break, which can make the current collector less likely to break during processing, thereby improving the manufacturing yield; and the composite current collector 10 can be used in the battery cell without the problem of pole piece breakage even under large expansion force or large deformation.

[0104] In some embodiments, the organic layer 11 includes an organic polymer film, which includes polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene ether, polyphenylene sulfide, polyethylene glycol, polysulfur nitride, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, phenolic resin and one or more of the derivatives, crosslinks and copolymers of the above polymers.

[0105] In some embodiments, the thickness of the organic layer 11 is 1 μm to 20 μm. It is understood that the thickness of the organic layer 11 can be, but is not limited to, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, and 20 μm.

[0106] In some embodiments, the thickness of the organic layer 11 is 3 μm to 10 μm.

[0107] The second aspect of the present application provides a secondary battery, which includes the composite current collector of the first aspect of the present application. The secondary battery of the present application uses the composite current collector 10 of the first aspect of the present application and has good rate performance and long-term stability.

[0108] A third aspect of the present application provides an electrical device, comprising the secondary battery of the second aspect of the present application.

[0109] The secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.

[0110] Unless otherwise specified, the components, material types or contents of the batteries mentioned are applicable to both lithium-ion secondary batteries and sodium-ion secondary batteries.

[0111] In one embodiment of the present application, a secondary battery is provided.

[0112] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0113] Positive electrode

[0114] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector.

[0115] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0116] In some embodiments, the positive electrode current collector may be the composite current collector of the first aspect of the present application.

[0117] In some embodiments, the positive electrode active material may include a positive electrode active material for a battery known in the art.

[0118] As an example, the positive electrode active material of a lithium-ion secondary battery may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0119] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the content of Li in the positive electrode plate is different when the battery is discharged to different states. In the list of positive electrode materials in this application, unless otherwise specified, the content of Li is the initial state of the material. The positive electrode material is applied to the positive electrode plate in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode material contained in the plate usually changes. Among them, the content of Li can be measured by molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry. It is understandable that the new material obtained by appropriate modification on the basis of the listed positive electrode materials is also within the scope of the positive electrode material. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode material, and non-limiting examples include coating modification.

[0120] In the list of positive electrode materials in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by molar content, but is not limited to this.

[0121] As an example, the positive electrode active material of the sodium ion secondary battery may include at least one of the following materials: at least one of a sodium transition metal oxide, a polyanionic compound, and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.

[0122] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1.

[0123] As an optional technical solution of the present application, the polyanionic compound can be a compound having sodium ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si; n represents (YO4) n- valence state.

[0124] Polyanionic compounds can also be those with sodium ions, transition metal ions, tetrahedral (YO4) n-A class of compounds containing anion units and halogen anions. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si, and n represents (YO4) n- valence state; the halogen may be at least one of F, Cl and Br.

[0125] Polyanionic compounds can also be sodium ions, tetrahedral (YO4) n- Anion unit, polyhedral unit (ZO y ) m+ and an optional halogen anion. Y can be at least one of P, S and Si, and n represents (YO4) n- valence state; Z represents a transition metal, which may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; m represents (ZO y ) m+ valence state; the halogen may be at least one of F, Cl and Br.

[0126] Polyanionic compounds include NaFePO4, Na3V2(PO4)3 (sodium vanadium phosphate, abbreviated as NVP), Na4Fe3(PO4)2 (P2O7), NaM'PO4F (M' is one or more of V, Fe, Mn and Ni) and Na3(VO y )2(PO4)2F 3-2y At least one of (0≤y≤1).

[0127] Prussian blue compounds can be sodium ions, transition metal ions and cyanide ions (CN - ). The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Prussian blue compounds are, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.

[0128] The weight ratio of the positive electrode active material in the positive electrode film layer is 80 to 100 weight %, based on the total weight of the positive electrode film layer.

[0129] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode film layer is 0 to 20 weight%, based on the total weight of the positive electrode film layer.

[0130] In some embodiments, the positive electrode film layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0-20% by weight, based on the total weight of the positive electrode film layer.

[0131] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, wherein the positive electrode slurry has a solid content of 40% by weight (wt%) to 80% by weight, and the viscosity at room temperature is adjusted to 5000 mPa·s to 25000 mPa·s, and the positive electrode slurry is coated on the surface of the positive electrode collector, and after drying, the positive electrode sheet is formed by cold rolling; the positive electrode powder coating unit surface density is 150 mg / m2 (mg / m 2 )~350mg / m 2 The compacted density of the positive electrode is 3.0 g / cm3 (g / cm 3 )~3.6g / cm 3 , optional 3.3g / cm 3 ~3.5g / cm 3 .

[0132] The calculation formula of the compacted density is:

[0133] Compacted density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).

[0134] The mass M of the positive electrode active material per unit area of ​​the positive electrode film can be obtained by weighing using a standard balance.

[0135] The thickness T of the positive electrode film can be measured by using a micrometer, for example, a Mitutoyo 293-100 micrometer with an accuracy of 0.1 μm. It should be noted that the thickness of the positive electrode film described in this application refers to the thickness of the positive electrode film in the positive electrode sheet used for assembling the battery after cold pressing.

[0136] Negative electrode

[0137] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0138] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0139] In some embodiments, the negative electrode current collector may be the composite current collector of the first aspect of the present application.

[0140] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery known in the art.

[0141] As an example, the negative electrode active material of the lithium ion secondary battery may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0142] As an example, the negative electrode active material of the sodium ion secondary battery is generally a hard carbon material, a two-dimensional metal carbide or a nitride. Preferably, the negative electrode active material of the sodium ion secondary battery is generally a hard carbon material.

[0143] The weight ratio of the negative electrode active material in the negative electrode film layer is 70 to 100 weight %, based on the total weight of the negative electrode film layer.

[0144] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode film layer is 0 to 30% by weight, based on the total weight of the negative electrode film layer.

[0145] In some embodiments, the negative electrode film layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode film layer is 0 to 20 weight %, based on the total weight of the negative electrode film layer.

[0146] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)), etc. The weight ratio of the other additives in the negative electrode film layer is 0 to 15 weight %, based on the total weight of the negative electrode film layer.

[0147] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry, wherein the solid content of the negative electrode slurry is 30wt% to 70wt%, and the viscosity at room temperature is adjusted to 2000mPa·s to 10000mPa·s; the obtained negative electrode slurry is coated on the negative electrode collector, and after a drying process, cold pressing such as rolling, a negative electrode sheet is obtained. The negative electrode powder coating unit area density is 75mg / m 2 ~220 mg / m 2 The compacted density of the negative electrode is 1.2 g / m3 (g / m 3 )~2.0g / m 3 .

[0148] The mass M of the negative electrode active material per unit area of ​​the negative electrode film can be obtained by weighing using a standard balance.

[0149] The thickness T of the negative electrode film can be measured by using a micrometer, for example, a Mitutoyo 293-100 micrometer with an accuracy of 0.1 μm. It should be noted that the thickness of the negative electrode film described in this application refers to the thickness of the negative electrode film in the negative electrode sheet used for assembling the battery after cold pressing.

[0150] Electrolytes

[0151] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0152] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0153] In some embodiments, the electrolyte salt of the lithium ion secondary battery can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0154] The electrolyte salt of the sodium ion secondary battery can be selected from one or more of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate, sodium perchlorate, and sodium chloride.

[0155] The concentration of the electrolyte salt is generally 0.5 mol / L to 5 mol / L.

[0156] In some embodiments, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0157] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0158] Isolation film

[0159] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0160] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0161] In some embodiments, the isolation film has a thickness of 6 μm to 40 μm, and may be 12 μm to 20 μm.

[0162] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0163] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0164] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0165] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Fig.12 The secondary battery 5 is a square structure as an example.

[0166] In some embodiments, reference Fig.13 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0167] In some embodiments, the secondary batteries 5 can be assembled into a battery module. The number of secondary batteries 5 contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0168] In the battery module, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0169] Optionally, the battery module may further include a housing having a housing space, and the plurality of secondary batteries 5 are housed in the housing space.

[0170] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0171] The battery pack may include a battery box and a plurality of battery modules disposed in the battery box. The battery box includes an upper box body and a lower box body, and the upper box body can be covered on the lower box body to form a closed space for accommodating the battery modules. The plurality of battery modules can be arranged in the battery box in any manner.

[0172] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0173] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0174] Fig.14 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0175] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0176] The following are some examples.

[0177] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the present application will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0178] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0179] 1. Implementation

[0180] Example 1

[0181] 1) Positive electrode

[0182] LiNi 0.8 Co 0.1 Mn 0.1 O2 and LiNi 0.5 Co 0.2 Mn 0.3 O2 is mixed in a ratio of 17:3 as the positive electrode active material. The positive electrode active material, superconductive carbon black SP as a conductive agent and polyvinylidene fluoride (PVDF) as a binder are dispersed in N-methylpyrrolidone (NMP) as a solvent in a mass ratio of 95:3:2 and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the composite current collector, and after drying, cold pressing, edge welding, die cutting, and striping, a positive electrode sheet is obtained.

[0183] 2) Negative electrode

[0184] The negative electrode active material graphite, superconductive carbon black SP as a conductive agent, SBR as a binder and CMC-Na as a thickener are dispersed in deionized water as a solvent in a mass ratio of 96:1:1:2 and mixed evenly to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil; after drying, cold pressing and slitting, a negative electrode sheet is obtained.

[0185] 3) Isolation film

[0186] A polyethylene film (PE) with a thickness of 9 μm was used as the base film of the diaphragm, and aluminum oxide, sodium carboxymethyl cellulose (CMC) and acrylate in a weight ratio of 93%:3%:4% were added to deionized water and stirred evenly under the action of a vacuum mixer to obtain a slurry with a solid content of 55%. The obtained slurry was evenly coated on the base film with a thickness of 2 μm on one side, and then PVDF was coated on both sides to obtain a diaphragm.

[0187] 4) Battery cell assembly

[0188] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain a bare battery cell, the pole ears are welded, the bare battery cell is installed in a square aluminum shell, and the top cover is laser welded.

[0189] 5) Battery filling

[0190] After vacuum baking at 100°C to remove water, the electrolyte is injected and sealed. After that, it is placed at 45°C, formed (charged at 0.02C constant current to 3.3V, then charged at 0.1C constant current to 3.6V), shaped and capacity tested to obtain the finished hard shell lithium ion battery.

[0191] Example 1 The positive electrode current collector is a composite current collector, the porosity of the metal layer is 3%, the pore size is between 10nm and 200nm, the proportion is 50%, the fracture strength of the organic layer is 305MPa, the thickness of the metal layer is 1μm, the metal element is aluminum, and the aluminum metal layer is deposited by vacuum coating, and the vacuum degree is about 1*10 -2 Pa, one-step coating forming method, some detailed collector parameters are shown in Table 1.

[0192] Example 2

[0193] This embodiment is basically the same as embodiment 1, with the main difference being that the porosity, roughness and specific surface area of ​​the metal layer in the positive electrode current collector are different, and the yield strength of the current collector is correspondingly different. In this embodiment, the metal layer has a porosity of 7%, a roughness of 0.23 μm, and a specific surface area of ​​0.192 g / m 2 The yield strength of the current collector is 161 MPa. Some detailed current collector parameters are shown in Table 1.

[0194] Example 3

[0195] This embodiment is basically the same as embodiment 1, with the main difference being that the porosity, roughness and specific surface area of ​​the metal layer in the positive electrode current collector are different, and the yield strength of the current collector is correspondingly different. In this embodiment, the porosity of the metal layer is 11%, the roughness is 0.25 μm, and the specific surface area is 0.195 g / m 2 The yield strength of the current collector is 150 MPa. Some detailed current collector parameters are shown in Table 1.

[0196] Example 4

[0197] This embodiment is basically the same as embodiment 1, with the main difference being that the porosity, roughness and specific surface area of ​​the metal layer in the positive electrode current collector are different, and the yield strength of the current collector is correspondingly different. In this embodiment, the porosity of the metal layer is 15%, the roughness is 0.27 μm, and the specific surface area is 0.201 g / m 2 The yield strength of the current collector is 141 MPa. Some detailed current collector parameters are shown in Table 1.

[0198] Example 5

[0199] This embodiment is basically the same as embodiment 1, with the main difference being that the porosity, roughness and specific surface area of ​​the metal layer in the positive electrode current collector are different, and the yield strength of the current collector is correspondingly different. In this embodiment, the porosity of the metal layer is 20%, the roughness is 0.29 μm, and the specific surface area is 0.21 g / m 2 The yield strength of the current collector is 120 MPa. Some detailed current collector parameters are shown in Table 1.

[0200] Example 6

[0201] This embodiment is basically the same as embodiment 1, with the main difference being that the metal layer of the positive electrode current collector is composed of two structures (dense layer + porous layer). The specific preparation method is to first use a slow deposition method to deposit a thin metal layer as a dense layer, with a single deposition amount of about 30nm and a thickness of 0.5μm; then use a fast deposition method to deposit a porous layer with a thickness of 0.5μm on the surface of the dense layer, with a single deposition thickness of 0.5μm. The porosity of the metal layer is 5%, the roughness is 0.21μm, and the specific surface area is 0.19g / m 2 , the current collector yield strength is 169MPa. Some detailed current collector parameters are shown in Table 1.

[0202] Example 7

[0203] This embodiment is basically the same as embodiment 6, with the main difference being that the thickness of the dense layer of the positive electrode current collector is 0.3 μm, the thickness of the porous layer is 0.7 μm, the porosity of the metal layer is 8%, the roughness is 0.23 μm, and the specific surface area is 0.193 g / m 2 , the current collector yield strength is 157MPa. Some detailed current collector parameters are shown in Table 1.

[0204] Example 8

[0205] This embodiment is basically the same as embodiment 7, with the main difference being that the thickness of the dense layer of the positive electrode current collector is 0.1 μm, the thickness of the porous layer is 0.9 μm, the porosity of the metal layer is 10%, the roughness is 0.24 μm, and the specific surface area is 0.194 g / m 2 , the current collector yield strength is 152MPa. Some detailed current collector parameters are shown in Table 1.

[0206] Example 9

[0207] This embodiment is basically the same as the embodiment 3, the main difference being that the material of the organic layer in the positive electrode current collector is different. The organic layer in the embodiment 9 is a PI (polyimide) film. Some detailed current collector parameters are shown in Table 1.

[0208] Embodiments 10 to 13

[0209] This embodiment is basically the same as embodiment 3, with the main differences being: the primary single crystal particle size, secondary single crystal particle size, and resistivity of the positive electrode current collector are different. Some detailed current collector parameters are shown in Table 2.

[0210] 2. Comparison

[0211] Comparative Example 1

[0212] This comparative example is basically the same as Example 1, with the main difference being that the positive electrode current collector is different. In Comparative Example 1, the positive electrode current collector adopts the composite current collector of the present application, and the metal layer of the composite current collector has a porosity of 0.5%, a roughness of 0.15 μm, and a specific surface area of ​​0.167 m 2 / g, yield strength of composite current collector σ s Some detailed current collector parameters are shown in Table 2.

[0213] Comparative Example 2

[0214] This comparative example is basically the same as Example 1, with the main difference being that the positive electrode current collector is different. In Comparative Example 2, the positive electrode current collector adopts the composite current collector of the present application, and the metal layer of the composite current collector has a porosity of 30%, a roughness of 0.35 μm, and a specific surface area of ​​0.246 m 2 / g, yield strength of composite current collector σ s Some detailed current collector parameters are shown in Table 2.

[0215] Comparative Example 3

[0216] This comparative example is basically the same as Example 13, with the main difference being that the positive electrode current collector is different. In Comparative Example 3, the positive electrode current collector adopts the composite current collector of the present application, which has a porosity of 0.5%, a roughness of 0.15 μm, and a specific surface area of ​​0.103 m 2 / g, and the yield strength is 165MPa. Some detailed current collector parameters are shown in Table 2.

[0217] 3. Test Method

[0218] 1) Pore size test

[0219] Take a surface sample, measure the diameter of the surface pores under SEM, and take the average value of multiple diameters.

[0220] 2) Porosity test

[0221] Take a fixed area S (e.g. 100cm 2 ) sample, using the true density tester (AccopycⅡ1340), using the PV=nRT formula, the true volume V1 of the current collector sample is obtained. Since the micropores inside the metal layer are wrapped by the surface metal, the gas cannot penetrate, so the true volume is larger than the theoretical volume of the densely packed metal. The true volume V1 includes two parts, one part is the volume V of the organic layer 有 (V 有 =S*T 有 , T 有 is the thickness of the organic layer), and one part is the volume of the metal layer V 金1 , V 金1 =V1-V 有 ; Theoretical density of metal layers tightly packed together ρ 金 , current collector weight m 集 and the density of the organic layer ρ 有 , organic layer thickness T 有 , the theoretical volume of the metal layer is calculated to be V 金2 (V 金2 =(m 集 -m 有 ) / ρ 金 ), where m 有 =ρ 有 *T 有 *S, porosity = (V 金1 -V 金2 ) / V 金1 .

[0222] 3) Composite current collector yield strength test

[0223] The tensile test was carried out using a tensile machine, with an initial distance of 50 mm and a speed of 50 mm / min. The inflection point of the curve can be read on the tensile curve as the yield strength.

[0224] 4) Organic layer breaking strength test

[0225] The tensile test was carried out using a tensile machine, with an initial distance of 50 mm and a speed of 50 mm / min, and the elongation corresponding to the fracture position was recorded.

[0226] 5) Resistivity test

[0227] Take samples for square resistance test, and then use a cross-section sample preparation machine to prepare cross-section samples, and then observe the thickness of the single-sided metal layer under SEM. Resistivity = square resistance * single-sided metal layer thickness.

[0228] 6) Grain size test

[0229] XRD was used for testing, and then the single crystal particle size was calculated using the Scherrer formula.

[0230] 7) Surface roughness test

[0231] The surface roughness is tested using a roughness meter to obtain the Ra value.

[0232] 8) Specific surface area test

[0233] The test was performed using the BET method.

[0234] 9) Test of square resistance growth rate after 10% elongation and stretching rebound

[0235] The current collector was cut into 15mm*150mm strips, and its initial surface square resistance was measured. Then it was stretched by 10%, and the surface square resistance of the first stretched area after stretching was tested. The growth rate = (square resistance after stretching - resistance before stretching) / resistance before stretching.

[0236] 10) Test of square resistance growth rate after 30% elongation and stretching rebound

[0237] The current collector was cut into 15mm*150mm strips, and its initial surface square resistance was measured. Then it was stretched by 30%, and the surface square resistance of the first stretched area after stretching was tested. The growth rate = (surface square resistance after stretching - resistance before stretching) / resistance before stretching.

[0238] 11) Elongation at break test

[0239] The current collector was cut into 15mm*150mm strips and subjected to tensile testing using a universal tensile testing machine with a gauge length of 50mm and a tensile speed of 50mm / min until the test piece broke. The average value of 10 strips was taken after testing.

[0240] 12) Battery cell DCR test

[0241] The battery cell is adjusted to 50% SOC, discharged at a rate of 4C (corresponding to discharge current I) for 30s, and the voltage difference ΔV before and after 30s discharge is recorded. The DCR corresponding to 50% SOC is calculated according to the following formula: DCR = ΔV / I, and the DCR data of each battery cell is obtained.

[0242] 13) Rate performance test

[0243] The fresh battery is fully charged at a rate of 0.33C at room temperature 25°C and then discharged. The discharge capacity at this time is recorded as the initial capacity C0. Then, the battery is discharged at a rate of 2C at room temperature 25°C. The discharge capacity at this time is recorded as C1. The capacity retention rate is calculated according to the following formula:

[0244] Capacity retention rate = C1 / C0×100%.

[0245] 14) Long-term stability test

[0246] A fresh battery cell is charged and discharged at a rate of 1C at a high temperature of 60°C until the capacity decays to 80% of the initial capacity, and the corresponding number of cycles is recorded to obtain the data of the number of cycles of each battery cell.

[0247] The parameters and performance test results of the above embodiments and comparative examples are shown in Table 1 and Table 2.

[0248] Table 1

[0249]

[0250]

[0251]

[0252]

[0253] Table 2

[0254]

[0255]

[0256] manual

[0257]

[0258] By comparing Examples 1 to 5 with Comparative Example 1, it can be seen that when the porosity is between 3% and 20%, the yield strength of the current collector is between 120 MPa and 180 MPa, which is less than the fracture strength of the organic layer of 305 MPa; 0.5*σ1*T 有 / (T 有 +T金 ) corresponds to 114MPa, 0.8*σ1*T 有 / (T 有 +T 金 ) corresponds to 183MPa; the yield strength is between the two, so that the tensile stress of the current collector shows a trend of slow increase, so the elongation at break is relatively high, greater than 50%; in comparative example 1, because the porosity is too low, only 0.5%, the yield strength of the current collector is relatively high (200MPa), exceeding 0.8*σ1*T 有 / (T 有 +T 金 ) corresponds to the range of 183MPa, so that the force on the current collector increases rapidly with the extension when it is stretched, so that the elongation at break is reduced (~35%); at the same time, since the elongation at break of Examples 1 to 5 is significantly higher than that of Comparative Example 1, the square resistance growth rate corresponding to the 10% stretching and 30% stretching of Examples 1 to 5 is lower than that of Comparative Example 1 (under the same extension conditions, Examples 1 to 5 are subjected to less force than Comparative Example 1), so that the battery cell performance of Examples 1 to 5 is better than that of Comparative Example 1, especially the long-term cycle performance. In the long-term cycle, the samples with a large tensile rebound square resistance growth rate have more surface cracks. During the use of the battery cell, the metal layer is more susceptible to corrosion reaction of the electrolyte, which makes the cycle performance of the battery cell worse.

[0259] By comparing Comparative Example 2 with Examples 1 to 5, it can be seen that the porosity of Comparative Example 2 reaches 30%. Due to the high porosity, the modulus of the metal layer is reduced, resulting in a decrease in the yield strength of the current collector (only 105 MPa). At this time, the reduction in yield strength has no obvious improvement on the elongation at break, but the yield strength is too low, resulting in increased elongation or other deformation of the current collector during cold pressing and other electrode processing, resulting in deformation of the electrode, resulting in poor interface performance of the battery cell, thereby resulting in deterioration of the DCR and rate performance of the battery cell, and the deterioration of the dynamics will also lead to deterioration of the long-term cycle performance.

[0260] Embodiments 6 to 8 include a dense layer and a porous layer, wherein the dense layer accounts for 10% to 50%. The thicker the dense layer, the higher the yield strength of the current collector, which makes the elongation at break of the current collector relatively lower. At the same time, due to the presence of the porous layer, the yield strength of the current collector is not too high. At the same time, the dense layer and the porous layer exist at the same time. The dense layer can effectively prevent the electrolyte from penetrating into the surface of the metal layer and the organic layer, and prevent the occurrence of the film stripping phenomenon, which is helpful for improving the long-term stability of the cycle of the battery cell (the number of cycles is higher than that of embodiments 1 to 5 with only a porous layer). At the same time, relative to comparative example 1 (only the case of a dense layer), the reduction in elongation caused by excessively high yield strength is effectively avoided, resulting in an increase in the growth rate of tensile rebound square resistance, and the deterioration of the performance of the battery cell is avoided. The presence of a dense layer and a porous layer can make the yield strength, elongation and electrical properties all at a good level.

[0261] Example 9: By changing the organic layer, higher elongation, better DCR, rate and cycle performance can still be achieved.

[0262] In Examples 3 and 10 to 12, the porosity is maintained at 11%, the difference is the primary single crystal particle size and the secondary particle size (primary single crystal particle size is 35 to 80 nm, secondary particle size is 90 to 300 nm), the yield strength is at a moderate level, and good ductility, tensile resilience and battery performance are obtained; the larger the primary grain size, the better the performance.

[0263] By comparing Example 13 and Comparative Example 3, it can be seen that when the metal layer is a copper layer, the porosity is in an appropriate range (5%), which can significantly improve the elongation at break of the copper composite current collector, thereby improving the performance of the battery cell; when the copper is close to a fully dense state (porosity 0.5%), due to the excessively high yield strength, the elongation at break is significantly reduced, which makes it easy to produce cracks during the stretching process, and the growth rate of the stretching rebound square resistance becomes larger, which increases the risk of cracking and breaking of the electrode during the long-term cycle of the battery cell, and deteriorates the battery cell performance (including DCR, rate and cycle performance).

[0264] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A composite current collector, characterized in that: comprising an organic layer and a metal layer disposed on at least one surface of the organic layer; The metal layer has pores, at least some of the pores have a pore size of 10 nm to 200 nm, and the porosity of the metal layer is 3% to 20%; The composite current collector satisfies the following relationship: 0.5*σ1*T 有 / (T 有 +T 金 )≤σ s ≤0.8*σ1*T 有 / (T 有 +T 金 ); Wherein, σ1 is the fracture strength of the organic layer, in MPa; T 有 is the thickness of the organic layer, in μm; T 金 is the total thickness of the metal layer, in μm; σ s is the yield strength of the composite current collector, in MPa.

2. The composite current collector according to claim 1, characterized in that: The metal elements in the metal layer include one or more of copper, aluminum, nickel, titanium, platinum, iron, cobalt, chromium, tungsten, molybdenum, magnesium, lead, indium and tin.

3. The composite current collector according to claim 1, characterized in that: The metal layer is a metal aluminum layer, and the composite current collector satisfies the following relationship: Wherein, ρ1 is the average density of the composite current collector, in g / cm 3 ; ρ2 is the density of the organic layer, in g / cm 3 .

4. The composite current collector according to claim 1, characterized in that: The composite current collector satisfies at least one of the following: (1) The yield strength of the composite current collector is 120 MPa to 180 MPa; (2) The resistivity of the composite current collector is ≤3.5*10 -8 Ωm; (3) The surface roughness of the composite current collector is ≥ 0.2 μm; (4) The specific surface area of ​​the composite current collector is ≥ 0.188 m 2 / g; (5) The square resistance growth rate of the composite current collector after 10% stretching and rebound is ≤5%; (6) The square resistance growth rate of the composite current collector after 30% elongation and stretching rebound is ≤10%; (7) The longitudinal elongation at break of the composite current collector is ≥40%; (8) The transverse elongation at break of the composite current collector is ≥40%.

5. The composite current collector according to claim 1, characterized in that: The size of the primary single crystal particles in the metal layer is 35nm to 80nm, and the size of the secondary particles in the metal layer is 90nm to 300nm.

6. The composite current collector according to claim 1, characterized in that: The thickness of the single metal layer is 0.5 μm to 5 μm; Optionally, the thickness of a single metal layer is 0.8 μm to 1.5 μm.

7. The composite current collector according to any one of claims 1 to 6, characterized in that: The single-layer metal layer includes a dense layer and a porous layer, the pores are located in the porous layer; the dense layer is arranged on the surface of the organic layer, and the porous layer is arranged on the surface of the dense layer away from the organic layer; or the porous layer is arranged on the surface of the organic layer, and the dense layer is arranged on the surface of the porous layer away from the organic layer.

8. The composite current collector according to claim 7, characterized in that: The density ρ3 of the dense layer is 2.65 g / cm 3 ≤ρ3≤2.70g / cm 3 The density of the porous layer is ρ4 2.00 g / cm 3 ≤ρ4<2.65g / cm 3 .

9. The composite current collector according to claim 7, characterized in that: The composite current collector satisfies at least one of the following: (9) The thickness of the dense layer is 10% to 50% of the thickness of the corresponding single-layer metal layer, and the thickness of the porous layer is 50% to 90% of the thickness of the corresponding single-layer metal layer; (10) The thickness of the dense layer is 100nm to 500nm; the thickness of the porous layer is 500nm to 900nm.

10. The composite current collector according to any one of claims 1 to 6, 8 or 9, characterized in that: The organic layer includes an organic polymer, and the organic polymer includes polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene ether, polyphenylene sulfide, polyethylene glycol, polysulfur nitride, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, phenolic resin and one or more of the derivatives, crosslinked products and copolymers of the above polymers.

11. The composite current collector according to any one of claims 1 to 6, 8 or 9, characterized in that: The thickness of the organic layer is 1 μm to 20 μm; Optionally, the thickness of the organic layer is 3 μm to 10 μm. 12 . A secondary battery comprising the composite current collector according to claim 1 .

13. An electrical device comprising the secondary battery according to claim 12.

Citation Information

Patent Citations

  • Porous silicon / carbon lithium ion battery negative electrode material and preparation method thereof

    CN112751007A

  • Lithium-repellent-lithium-loving 3D gradient current collector and preparation and application thereof

    CN116053482A

  • Conductive film and preparation method thereof

    CN116313237A

  • Thermally stable polymer-based composite separator for a lithium secondary battery and manufacturing method

    US20220384909A1

  • Lithium-ion battery with anode comprising blend of intercalation-type anode material and conversion-type anode material

    WO2021203086A1